The Impact of Remittances on Poverty Alleviation in Selected Emerging Markets - Tsaurai, Kunofiwa (Comparative Economic Research. Central and Eastern Europe, 2018)
The study explored the impact of remittances on poverty in selected emerging markets. On the theoretical front, the optimistic view argued that remittances inflow into the labour exporting country reduces poverty whereas the pessimistic view proponents said that remittances dependence syndrome retards both economic growth and income per capita. Separately, using two measures of poverty [the poverty headcount ratio at US 1.90 and US 3.10 a day (% of population)] as dependent variables, the fixed effects approach produced results which supported the remittances led poverty reduction (optimistic) hypothesis whereas the pooled ordinary least squares (OLS) framework found that remittances inflow into the selected emerging markets led to an increase in poverty levels. The implication of the findings is that emerging markets should put in place policies that attract migrant remittances in order to reduce poverty levels. They should avoid over‑reliance on remittances as that might retard economic growth and income per capita.